Overcoming the Economic Crisis due to a Pandemic through Islamic Finance - Muhammad Ammar Ashraf (Journal of Islamic Economics Lariba, 2021)
The Covid-19 disaster is an exogenously induced downturn that is expected to leave 2021 global GDP approximately 5 percentage points lower than in January 2020 pre-Covid-19 estimates. The negative impact on low-income households is especially severe, jeopardizing the world's significant progress in reducing extreme poverty since the 1990s. To react to frequent crises and catastrophe global economic stagnation, a new paradigm is required. Institutionalized risk-sharing can assist the global economy in resiliently absorbing shocks and stimulating stagnant demand. Islamic finance principles assist the economy in avoiding endogenously generated crises, such as the Global Financial Crisis, and provide a strong safety net against exogenously induced cycles, such as the Covid-19 crisis. In practice, this necessitates a diverse set of well-functioning institutions to translate these principles into real-world impact. As it currently stands, the Islamic financial industry’s many essential components of this spectrum are still missing. The crisis should be viewed as an opportunity to fill gaps and diversify the industry. Given the fact that the Covid-19 crisis is exogenously induced, the impact on Islamic banks is expected to be comparable to that on conventional banks. The similarity of their business model, sharia-compliant equities, on the other hand, outperformed their conventional counterparts. The ineffectiveness of non-profit organizations, like awqaf and zakat, reduced the role of the safety net in curbing the repercussions of the crisis. The Covid-19 pandemic poses liquidity, resilience, and capital challenges for the Islamic banking sector.